Analisis Daya Dukung Tanah Pondasi Tiang Pancang Berdasarkan Uji Sondir: Analysis of the Bearing Capacity of Piled Foundation Soil Based on Sondir Test - Diharyo; Rudy Yoga Lesmana; Achmad Imam Santoso (Jurnal Teknik SILITEK, 2024)
His research aims to get a clear picture of the bearing capacity of the soil as a basis for foundation calculations. The bearing capacity of the soil is the ability of the soil to withstand the load of the building without experiencing excessive settlement. Field testing is carried out using two main methods, namely the Boring Test and Standard Penetration Test (SPT) as well as laboratory tests to analyze the physical and mechanical properties of the soil. From the test results at a depth of 15 - 22 meters, it was found that the density of the hard soil was of a clay-silty to sandy type. The foundation used was a deep foundation (Deep Foundations), namely a pile foundation or (Bore Pile) with a size of 40 cm x 40 cm or Bore foundation. Pile to his size 50 cm.